Sosialisasi Menabung Sejak Dini dan Berwirausaha Pada Usia Muda di Desa Hutaimbaru - Yusril Ihza Mahendra; Mutholib Mutholib (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
. Economics is one of the fields of social science, economics is associated with the activities of human behavior in the necessities of life. Entrepreneurship is an innovator as an individual who has the instinct to see opportunities, has the spirit, ability and mind to conquer slow and lazy ways of thinking. From the description above, it can be concluded that entrepreneurship is one way to see opportunities. Talking about opportunities in entrepreneurship requires a strategy to be able to develop a business in realizing economic independence. In this activity, the entire community in Hutaimbaru Village fulfills their needs, and their livelihoods as farmers, both as rubber farmers, vegetable farmers, and traders, but to this day the condition of the Hutaimbaru village community is still classified as middle to lower economy, because they are still Many of these people work in one day and can spend the night to meet the needs of their families. With the socialization activity, the Hutaimbaru village community increased their efforts to increase the businesses of the residents who were experiencing a decline due to the COVID-19 pandemic.